Pengaruh Pemberian Kuis Awal pada Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) terhadap Motivasi dan Hasil Belajar Siswa Kelas X SMAN 11 Makassar (Studi pada Materi Pokok Ikatan Kimia) - Fahmi, Nurul; Wijaya, Mohammad; Danial, Muhammad (ChemEdu, 2021)
The research is quasi experiments that aim to know the influence of pre-quiz giving using NHT type cooperative learning model towards motivation and achievement of X grade student of SMAN 11 Makassar. The independent variable are NHT type cooperative learning model with pre-quiz and without pre-quiz giving in cooperative learning model, and dependent variable are students’ motivation and achievement in chemical bonding main subject of learning. The population is whole student of X Grade SMAN 11 Makassar. The samples include two classes such as X2 as an experiment class with 36 students and X1 class as a control class with 34 students. The result of the research is obtained by giving motivation questionnaire and learning achievement test in chemical bonding subject which from as post-test and analyzed by using t-test. The result of inferential statistic analysis for learning motivation shows tcount (1,48) > ttable (1,828) at α= 0,05. And the result of inferential statistic for achievement test shows tcount (2,625) > ttable (1,674) at α= 0,05. According to the result of data analysis shows that pre-quiz in NHT type of cooperative learning model influences motivation and achievement of X grade student of SMAN 11 Makassar in main subject of chemical bonding.